Characterization of cross-linked enzyme aggregates (CLEA)-amylase from Zophobas morio - Easa, Muhammad Noor; Yusof, Faridah; Abd Halim , Amanatuzzakiah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Cross-Linked Enzyme Aggregates (CLEA) is known as one of the best enzyme immobilization technique to date. In this study, amylase extract from Zophobas morio (supermeal worm) larvae was immobilized using acetone as the precipitant, glutaraldehyde as the cross-linker and bovine serum albumin as the additive. The characteristics of the produced CLEA was compared to its’ soluble counterpart, in terms of pH and temperature optimum and stabilities. The results showed that CLEA and free amylase had optimum temperature at 55°C and 45°C, respectively. CLEA-amylase displayed greater stability against high temperature as compared to free enzyme which has lost most of its activity when the temperature was set beyond 45°C. At 65°C, CLEA-amylase still retained 73.2% of its activity. Results also showed that, CLEAamylase exhibited pH optimum at 11, while it is 7 for free enzyme. Similarly, CLEA-amylase more stable than the free form, over a wider range of pH, particularly at higher pH of 9, 10 and 11. Recyclability study showed that CLEA-amylase can retain 14.9% of its residual activity after 6 times of repeated uses. Since it is reusable, future works might include the evaluations of using CLEA-amylase at industrial level, remarkably in detergent applications.